FAKTOR DETERMINAN KEMENANGAN KANDIDAT PADA PEMILUKADA KABUPATEN BATANG 2011 - FITRIYAH DKK FITRIYAH DKK (Politika: Jurnal Ilmu Politik, 2014)
Today head local elections not by the legislature  body but  by the people is  improve the quality of local democracy, because the people involved in determining who becomes the heads. In determining the choice of the people having these considerations, it is not always the candidate who carried the major parties win elections. This study intends to find out what factors are significant actual or prospective determinant decisive victory in the Batang Head Local Election 2011, after previous similar studies conducted in Semarang City Election, 2010. This type of research is a descriptive analysis, conducted on 120 respondents from voters selected by multistage random sampling technique. The data was collected using questionnaire techniques, interview and documentary study. Quantitative data were obtained from a questionnaire prepared by the descriptive statistical analysis so that can know the frequency distribution. While the qualitative data obtained from open-ended questions were processed and classified according to their degree of importance. The study found a figure significantly influence candidate winning candidate in the Batang Head Local Election  2011. While the sociological factors, psychological factors and the  economic factors influence, but not significant. This study also found that voters consider  money politics for granted, but the money was not a major factor for consideration in choosing a candidat.